'20s & '30s style - Horsham, Michael (Grange Books, 1994)
This illustrated book explores the 1920s and 1930s from rising hemlines to streamlined trains, from Fred Astaire to Adolf Hitler, and more.
Keywords: 1920-luku; 1930-luku; kulttuurihistoria; tyylit; elämäntapa; historia; arkkitehtuuri; art deco; julistetaide; muoti; muotoilu; sisustus; taidehistoria; aikakaudet; modernismi; kulturhistoria; modernism